“Hoje é dia de passagem!”: uma etnografia sobre a construção de laços entre pessoas e entidades a partir de uma prática religiosa doméstica - MACHADO, Julyana Ketlen Silva (2023)
This dissertation aims to understand how the bonds between people and entities are built, intensified, and configured from a domestic religious practice that is carried out in everyday life, and is driven by it. Everyday life appears as a space in which religion manifests itself more effusively and my focus here is a house that starts to carry out a passage for the development of entities and people, during the Covid-19 pandemic. People and spirits share everyday life, whose experiences allow us to understand, among other issues, relationships of belonging, affiliation, respect, solidarity, trust, devotion - and, equally, relationships of conflict and power present in the configurations of blood and spiritual kinship. In this sense, home represents a place of meeting and cohabitation capable of offering significant elements about human life and its relationship with the sacred.